DÉVELOPPEMENT DU MÉDIA D'APPRENTISSAGE DE LA MÉTHODE VERBO-TONALE DANS L'ENSEIGNEMENT DE LA PRONONCIATION POUR LES APPRENANTS DU FLE - Analeila Devira Lorenzi, - (2021)
This research is conducted with a purpose to design and develop a learning product related to one of phonetic correction called verbotonal. The learning product is in the form of learning video for learning French pronunciation. This product is expected to be able to overcome the problems of students in learning French pronunciation. This study aims to describe: (1) the development of the learning media based on the verbotonal method in the pronunciation teaching, (2) the steps in the development of the learning media based on the verbotonal method of phonetic correction in pronunciation learning and (3) the opinions of students and teachers on the development of the learning media based on the verbotonal method in pronunciation learning. This study uses the Research and Development (R&D) method with the Plomp model which includes five stages, namely: (1) prelimenary investigation, (2) design, (3) realization/construction, (4) test, evaluation and revision and (5) implementation. The population in this study are all pronunciation subjects, while the sample in this study is the material on nasal vowels, oral vowels, semi-vowels and consonants. The result of this research is the creation of a development of the learning media based on the verbotonal method in the form of a video as a learning tool for FLE learners which can be used by other French teachers and also accessible on the Youtube channel [Analeila Devira Lorenzi]. Based on the result, we can conclude that (1) students were interested in practicing or learning more about pronunciation in French ; (2) the material in the learning video is clear and easy to understand and (3) the phonetic transcription contained in the video is worth writing because it can help students support French pronunciation skills.